2020
DOI: 10.1364/optica.393035
|View full text |Cite
|
Sign up to set email alerts
|

Chiral topological photonics with an embedded quantum emitter

Abstract: This is a repository copy of Chiral topological photonics with an embedded quantum emitter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…After that, Mehrabad et al also experimentally demonstrated a chiral ring resonator in valley photonic crystal of honeycomb lattice on GaAs slab with an embedded layer of InGaAs quantum dots [94]. The topological structure with a beardedshaped interface is displayed in Figure 4F.…”
Section: Chiral Topological Quantum Interface Based On Photonic Quantum Valley-hall Effectmentioning
confidence: 95%
See 1 more Smart Citation
“…After that, Mehrabad et al also experimentally demonstrated a chiral ring resonator in valley photonic crystal of honeycomb lattice on GaAs slab with an embedded layer of InGaAs quantum dots [94]. The topological structure with a beardedshaped interface is displayed in Figure 4F.…”
Section: Chiral Topological Quantum Interface Based On Photonic Quantum Valley-hall Effectmentioning
confidence: 95%
“…Additionally, a new class of topologically engineered photonic crystal waveguides have been proposed and demonstrated recently, the guided modes of which have been identified as both chiral [6,11] and resistant to back-scattering in 60-degree bends [71,81,[93][94][95]. Quantum chiral-light matter interface has been demonstrated based on the quantum spin-Hall effect [96].…”
Section: Chiral Topological Quantum Interface Based On Photonic Quantum Spin-hall Effectmentioning
confidence: 99%
“…The topological cavities based on the first approach have found applications in chiral quantum optics. [ 118,119 ] Such topological cavities supporting two counter‐propagating modes with opposite polarization can be strongly coupled to a solid‐state quantum emitter. Due to the chiral coupling between the topological cavity and the quantum emitter, the emitter emits preferably into CW or CCW running modes depending on its spin (see Figure 10c).…”
Section: Topological Cavities and Lasersmentioning
confidence: 99%
“…The combination of topology with quantum regime will bring more interesting phenomena and physics [45][46][47][48][49]. Especially, the coupling between quantum emitters and topologically protected state will exhibit robust strong light-matter interaction, enabling a topological quantum optics interface [50,51]. For example, the coupling to topological edge state enables the robust chiral emission of quantum dots (QDs) [50].…”
Section: Introductionmentioning
confidence: 99%